2012
DOI: 10.1017/s1742646412000209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the quality of care in psychiatric intensive care units and acute psychiatric wards

Abstract: Background: Literature comparing the quality of care on psychiatric intensive care units and acute wards is sparse, but a review has found differences in key areas e.g. violence, drugs and alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…An environment in which multidisciplinary care and treatment can be delivered safely is created through high levels of physical, relational and procedural security, for which nursing staff (qualified and unqualified) often carry the burden of responsibility (McAllister & McCrae 2017). Despite the lack of coherency or underpinning ideology identified, there is little evidence to suggest that quality of patient care is compromised, as compared to other inpatient settings (Lemmey et al 2013). There is a limited but notable amount of evidence to suggest that treatment outcomes are positive for patients who are in acute psychiatric distress (Gwinner & Ward 2013), but an absence of understanding of the mechanisms that bring about change (Hayes et al 2017).…”
Section: State Of Research On Camhs Picumentioning
confidence: 99%
“…An environment in which multidisciplinary care and treatment can be delivered safely is created through high levels of physical, relational and procedural security, for which nursing staff (qualified and unqualified) often carry the burden of responsibility (McAllister & McCrae 2017). Despite the lack of coherency or underpinning ideology identified, there is little evidence to suggest that quality of patient care is compromised, as compared to other inpatient settings (Lemmey et al 2013). There is a limited but notable amount of evidence to suggest that treatment outcomes are positive for patients who are in acute psychiatric distress (Gwinner & Ward 2013), but an absence of understanding of the mechanisms that bring about change (Hayes et al 2017).…”
Section: State Of Research On Camhs Picumentioning
confidence: 99%
“…Still, these studies demonstrate that PICU patients improved dramatically in symptomatology compared to patients in acute wards (Cohen & Khan 1989). However, a more recent study comparing the quality of care between PICU and acute wards found no significant differences (Lemmey et al 2012). Although PICU are established to provide care for patients with the worst phases of mental illness, relatively few studies have examined this subspecialty.…”
Section: Introductionmentioning
confidence: 96%
“…However, a more recent study comparing the quality of care between PICU and acute wards found no significant differences (Lemmey et al . ). Although PICU are established to provide care for patients with the worst phases of mental illness, relatively few studies have examined this subspecialty.…”
Section: Introductionmentioning
confidence: 97%